BRF Negatively Regulates Thermotolerance Defect of fes1a in Arabidopsis - Fu, Can; Liu, Xiaxia; Li, Xuezhi; Huo, Panfei; Ge, Jingjing; Hou, Yanfei; Yang, Wenwen; Zhang, Jingxia; Zhang, Limin; Zhao, Dazhong; Ma, Changle; Liu, Jian (Frontiers in Plant Science, 2020)
FES1A is a heat shock protein 70 binding protein. Mutation of FES1A leads to a defect in thermotolerance of Arabidopsis; however, independent fes1a mutants exhibit a range in the extent of thermosensitivity. Here, we found that BRF2, a gene adjacent to FES1A and encoding a component of transcription factor IIIB, affects the thermosensitivity of fes1a mutants. Knock out of BRF2 suppressed fes1a thermosensitivity, while overexpression of BRF2 increased thermosensitivity of fes1a. BRF2 in fes1a mutants regulates the transcriptional strength of RNA Polymerase II and many of protein synthesis-related pathways as well, and eventually affects the thermotolerance of fes1a. There is a cross-talking between RNA Pol III and Pol II. The cross-talking is initiated by BRF, magnified by the mutation of FES1A and finally has an effect on thermotolerance.